Waste Sorting Behavior Among Students: Testing the Effects of Visual Prompts - Uye, Emmanuel Etim; Olapegba, Peter Olamakinde (International Journal of Research and Community Empowerment, 2025)
Garbage has various categories so it needs to be sorted to make it easier to sort according to its benefits. However, waste sorting is very difficult to implement for some people including in the school environment. Therefore, the objective of this study was to test the effects of visual prompt on waste sorting behavior among students in selected secondary schools in Lagos, Nigeria. Quasi-experimental design was adopted while visual prompt was manipulated at three levels of word, picture and word+ picture to obtain data on waste sorting behavior among 240participants. Data collected were analyzed using descriptive and inferential statistics to test one hypothesis which was accepted at p <.001 level of significance. The result demonstrated that picture was the most effective visual prompt that improved waste sorting behavior followed by word + picture prompt and then word prompt compared to the control group. The study concluded that visual prompt improved waste sorting behavior. The novelty of this study is that it is the first time effects of visual prompt on waste sorting behavior is studied using quasi-experimental design in Nigerian schools. The study recommended that school authority and other stakeholders’ interested in solid waste management should design appropriate visual prompts to encourage waste sorting activities in their school environments.